AtbHLH68 transcription factor contributes to the regulation of ABA homeostasis and drought stress tolerance in Arabidopsis thaliana. Issue 3 (29th March 2017) - Le Hir, Rozenn; Castelain, Mathieu; Chakraborti, Dipankar; Moritz, Thomas; Dinant, Sylvie; Bellini, Catherine
Abstract : Basic helix‐loop‐helix (bHLH) transcription factors are involved in a wide range of developmental processes and in response to biotic and abiotic stresses. They represent one of the biggest families of transcription factors but only few of them have been functionally characterized. Here we report the characterization of AtbHLH68 and show that, although the knock out mutant did not have an obvious development phenotype, it was slightly more sensitive to drought stress than the Col‐0, and AtbHLH68 overexpressing lines displayed defects in lateral root (LR) formation and a significant increased tolerance to drought stress, likely related to an enhanced sensitivity to abscisic acid (ABA) and/or increased ABA content. AtbHLH68 was expressed in the vascular system of Arabidopsis and its expression was modulated by exogenously applied ABA in an organ‐specific manner. We showed that the expression of genes involved in ABA metabolism [ AtAAO3 ( AtALDEHYDE OXIDASE 3) and AtCYP707A3 ( AtABSCISIC ACID 8′HYDROXYLASE 3)], in ABA‐related response to drought‐stress ( AtMYC2, AtbHLH122 and AtRD29A ) or during LRs development ( AtMYC2 and AtABI3 ) was de‐regulated in the overexpressing lines. We propose that AtbHLH68 has a function in the regulation of LR elongation, and in the response to drought stress, likely through an ABA‐dependent pathway by regulating directly or indirectly components of ABA signaling and/or metabolism.